Method for Calculation of Steam-Compression Heat Transformers - S. V. Zditovetckaya; V. I. Volodin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a method for joint numerical analysis of cycle parameters and heatex-change equipment of steam-compression heat transformer contour that takes into account a non-stationary operational mode and irreversible losses in devices and pipeline contour. The method has been realized in the form of the software package and can be used while making design or selection of a heat transformer with due account of a coolant and actual equipment being included in its structure.The paper presents investigation results revealing influence of pressure loss in an evaporator and a condenser from the side of the coolant caused by a friction and local resistance on power efficiency of the heat transformer which is operating in the mode of refrigerating and heating installation and a thermal pump. Actually obtained operational parameters of the thermal pump in the nominal and off-design operatinal modes depend on the structure of the concrete contour equipment.